Exercise induced neuroplasticity to enhance therapeutic outcomes of cognitive remediation in schizophrenia: Analyzing the role of brain-derived neurotrophic factor - Campos, C. (2017)
Cognitive impairment is a major manifestation of schizophrenia and a crucial treatment target as these deficits are closely related to patients' functional outcomes. Cognitive remediation is the gold-standard practice to address cognitive deficits in schizophrenia. There is clear evidence stating that cognitive remediation improves cognitive function and promotes structural neuroplastic changes in patients with schizophrenia, with brain-derived neurotrophic factor (BDNF) expression emerging as a potential biomarker for its efficacy. This is particularly important as there is clear evidence relating atypical BDNF expression to cognitive impairment in patients with schizophrenia. Despite the valuable role of cognitive remediation in the management of schizophrenia, there is still a need to develop methods that allow maximizing its efficacy.